Viscous deformation of geosynthetic reinforcement under cyclic loading conditions and its model simulation. Issue 2 (April 2004) - Kongkitkul, W.; Hirakawa, D.; Tatsuoka, F.; Uchimura, T.
Abstract : To evaluate the deformation characteristics of geosynthetic reinforcement under cyclic loading conditions, a series of tensile loading tests were performed on three types of polymer geogrid and one type of geocomposite using a wide variety of loading histories, including cyclic loading and sustained loading applied during otherwise monotonic loading. In order to separate the loading rate effects due to viscous properties from the rate-independent cyclic loading effects, cyclic loading was applied at five different frequencies for the same total period of cyclic loading at several base loads using two different load amplitudes. It is shown that the residual strain that develops during a given cyclic loading history is controlled essentially by the total period of cyclic loading, whereas it is independent of loading frequency (i.e. independent of the number of loading cycles). That is, the residual strain that develops during a given cyclic loading history is due mostly to the intrinsic viscous properties of the respective geosynthetic reinforcement type. The whole relationship between the tensile load and the tensile strain measured from the start to the end of the respective test, which consisted of monotonic loading and cyclic or sustained loading or both, was successfully simulated by a non-linear three-component rheology model with parameters that do not incorporate any rate-independent cyclic loading effects.